SUBSTRATE MIXING FORMULATIONS FOR CITRUS NURSERY MANAGEMENT (Nativa, 2023)
ABSTRACT:  The citrus seedling development is determined by several factors, including the physical and chemical qualities of the substrate, which affect the quality of field seedlings. The purpose of this study was to evaluate how the ‘Swingle’ citrumelo rootstock developed with different substrate formulations. The experiment was carried out in a seedling nursery from seeding to grafting, and six treatments were carried out: 60% peat moss, 30% fine grade horticultural vermiculite, 10% rice hulls; 60% peat moss, 30% super fine grade horticultural vermiculite, 10% rice hulls ; 50% peat moss, 30% fine grade horticultural vermiculite, 20% rice hulls ; 50% peat moss, 30% super fine grade horticultural vermiculite, 20% rice hulls ; 50% peat moss, 20% fine grade horticultural vermiculite, 30% rice hulls ; 50% peat moss, 20% super fine grade horticultural vermiculite, 30% rice hulls.  When container transplanting was performed, the emergence percentage of seedlings was determined. Stem height, stem diameter, leaf number, area meter, root dry matter, leaf and stem dry matter, and quality index were measured on seedlings. All substrate formulations improved seedling development until grafting, except for the formulations with 30% rice hulls, which hampered seedling development in ‘Swingle' citrumelo.Keywords: [Citrus paradisi Macfad. Duncan grapefruit × Poncirus trifoliata (L.) Raf.]; peat moss; rice hulls; vermiculite. Manejo de viveiro de citros com mistura de formulações de substrato RESUMO: Muitos fatores influenciam na formação das mudas cítricas, sendo que as propriedades físicas e químicas dos substratos afetam a qualidade da muda levada a campo. O trabalho teve como objetivo avaliar o desenvolvimento do porta-enxerto citrumeleiro ‘Swingle’ em diferentes formulações de mistura de substratos. O experimento foi realizado em viveiro sendo as plantas conduzidas da semeadura até o ponto de enxertia. Os tratamentos utilizados foram: Substrato 60% Turfa Sphagnum, 30% vermiculita fina, 10% casca de arroz; Substrato 60% Turfa Sphagnum, 30% vermiculita super fina, 10% casca de arroz; Substrato 50% Turfa Sphagnum, 30% vermiculita fina, 20% casca de arroz; Substrato 50% Turfa Sphagnum, 30% vermiculita super fina, 20% casca de arroz; Substrato 50% Turfa Sphagnum, 20% vermiculita fina, 30% casca de arroz; Substrato 50% Turfa Sphagnum, 20% vermiculita super fina, 30% casca de arroz. No tranplantio, foi avaliada a porcentagem de emergência das plântulas. Foram avaliadas altura das plantas, diâmetro do caule, número de folhas, área foliar, massa seca das raízes e parte aérea e índice de qualidade. Todas as formulações de mistura de substratos proporcionam desenvolvimento semelhante das mudas até a enxertia, exceto as formulações com 30% de casca de arroz que não promoveram o desenvolvimento adequado das plântulas de citrumeleiro ‘Swingle’.Palavras-chave: [Citrus paradisi Macfad. Duncan grapefruit × Poncirus trifoliata (L.) Raf.]; casca de arroz vermiculita; turfa de Sphagnum.